THE INFLUENCE OF THE KARTINI FILM ON GENDER EQUALITY PERSPECTIVES: A CASE STUDY OF ADOLESCENTS AT SMAN 24 CENTRAL JAKARTA - Syatri, Nadhira; Suni, Eugenius Kau (Transpublika Publisher, 2024)
In Javanese society, women are traditionally expected to embody qualities like gentleness, obedience, and loyalty. Indonesian culture dictates specific roles for men and women, with men typically occupying public spaces and women confined to domestic spaces. The film Kartini represents a modern resistance against patriarchal norms by showcasing women's equal capabilities and potential contributions in various sectors, challenging societal expectations. By portraying women as equally capable in domestic and public spheres, the film challenges the prevailing patriarchal culture in Indonesian society. The main focus of the current study will be to focus on the Kartini film in knowing the effect it produces on the perspective of gender equality. This research will be useful based on two aspects, namely academic benefits and practical benefits. The expected practical benefit is that the results of this study can be useful for students to change their perspective on gender equality, and academic benefits can also be taken, namely to make this research as a basis for students if they will conduct research that is in line with this discussion. In the context of the current research using quantitative methods by involving active respondents from SMAN 24 Jakarta students. The data collection process uses a questionnaire distributed through the Google Forms link and then processed using a simple linear analysis technique. The results showed that the Kartini film had a significant influence on the Gender Equality Perspective of Adolescents at SMAN 24 Jakarta.